Winners and Losers of Immigration - Davide Fiaschi; Cristina Tealdi (Institute of Labor Economics (IZA), 2020)
We aim to identify winners and losers of a sudden inflow of low-skilled immigrants using a general equilibrium search and matching model in which employees, either native or nonnative, are heterogeneous with respect to their skill level and produce different types of goods. We estimate the short-term impact of this shock for Italy in the period 2008-2017 to be sizeable and highly asymmetric. In 2017, the real wages of low-skilled and high-skilled employees were 8% lower and 4% higher, respectively, compared to a counter-factual scenario with no non-natives. Similarly, employers working in the low-skilled market experienced a drop in profits of comparable magnitude, while the opposite happened to employers operating in the high-skilled market. Finally, the presence of non-natives led to a 10% increase in GDP and to an increment of approximately 70 billions exteuro in Government revenues and 18 billions exteuro in social security contributions. We argue that these results help rationalise the recent surge of anti-immigrant sentiments among the low-income segment of the Italian population.
Keywords: J61; J64; J21; J31; 330; immigration; welfare; search and matching